FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JERUK SIAM DI DESA TARO KECAMATAN TEGALLALANG KABUPATEN GIANYAR - Ni Gst. Ag. Gde Eka Martiningsih; Ni Putu Sukanteri; Rosita Lagut (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
Indonesia is a wealthy country with thousands of islands and vast stretches of ocean.  Agriculture is a sector that plays a major role and influence in economic growth in Indonesia.  The agricultural sector consists of several subsector such as food crops, horticulture, forestry, plantations.  livestock and fisheries.  Horticulture is a subsector that has quite large potential for development.  Orange plant is one of the horticultural commodities.  Orange is a type of fruit that is most popular for Indonesian people.  The aim of this research is to improve production factors and characteristic factors that influence the production of Siam Oranges in Taro Village, Tegalalang district, Gianyar Regency.  This research was carried out in Taro Village, Tegalalang district, Gianyar Regency.  The respondents for this research were 30 farmers.  The method used in this research were descriptive and quantitative analysis and location selection was carried out by purposive sampling, that is deliberately.  The data sources in this research are primary and secondary data.  The analysis used in this research are  descriptive and quantitative analysis.  The results of this research were obtained in Taro Village, Tegalalang District, Gianyar Regency. The production factors that had a significant effect were the variable land area, organic fertilizer, inorganic fertilizer and pesticides, while the labor variable had no significant effect on the production of Siamese oranges.  Farmer factors, those are age, education, length of farming, number of family members, have no significant effect on Siamese orange production.